How strong is the impact of exports and other demand components on German import demand? Evidence from euro-area and non-euro-area imports - Claudia Stirböck (Deutsche Bundesbank, 2006)
This paper presents a single error-correction analysis of German total, euro-area (intra) and non-euro-area (extra) import demand for the 1980-2004 period and the more recent 1993-2004 period. German import demand is mainly driven by domestic demand and foreign demand for German goods; by contrast, the price sensitivity of German imports is low. We note a greater propensity to import with respect to an increase in investment compared to a rise in consumption, yet find that export goods have the highest marginal import content. The influence of export demand on the German economy's import demand is growing, with the marginal propensity to import being higher for extra imports than for intra imports; in addition, the reagibility of the former has intensified perceptibly since the 1990s. The price sensitivity of intra imports is not only higher but, unlike that of extra imports, is also significant and has increased at the current end.
Keywords: C22; E20; F41; 330; Import demand; intra and extra euro-area imports; import content; single equation error-correction; Importnachfrage; Gesamtwirtschaftliche Nachfrage; Export; Preiselastizität; Schätzung; Deutschland